Hydrogenation of Esters to Alcohols with a Well‐Defined Iron Complex. Issue 33 (30th May 2014) - Werkmeister, Svenja; Junge, Kathrin; Wendt, Bianca; Alberico, Elisabetta; Jiao, Haijun; Baumann, Wolfgang; Junge, Henrik; Gallou, Fabrice; Beller, Matthias
Abstract We present the first base‐free Fe‐catalyzed ester reduction applying molecular hydrogen. Without any additives, a variety of carboxylic acid esters and lactones were hydrogenated with high efficiency. Computations reveal an outer‐sphere mechanism involving simultaneous hydrogen transfer from the iron center and the ligand. This assumption is supported by NMR experiments.